Analisa Respon Antilock Braking System(ABS) dan Energi yang Dibutuhkan Selama Proses Pengereman pada Jalan Menurun - Edoward R., Mochamad; Guntur, Harus Laksana (ROTOR, 2013)
The process of braking on downhill roads require greater energy due to the influence of gravity work by vehicle due to the tilt angle . This paper reports the results of modeling and simulation responses ABS and energy required during braking on a straight - path trajectory decreases. Vehicles with ABS modeled mathematically to obtain the dynamic equations of the system. With the Laplace transform transfer function obtained from the vehicle with ABS. And with the help of MATLAB SIMULINK software obtained response vehicle speed, wheel speed, wheel slip, braking distance, and the energy required during the braking process. In this study used the roadway with a variation of the angle Î¸ decreases of 100, 200, 300. Assuming the initial speed of the vehicle at 40kph , it can be concluded that the simulation results show stopping distance was 31.08m, 32.96m, 34.77m with a stop time for 5.169s, 5.325s, 5.464s sequentially in order of angular variation. While the maximum power required during the braking process is 1.88kW, 3.71kW, 5.44kW. The results of calculation of the energy required during the braking process can be used as a reference in planning a regenerative braking system, the utilization of the energy wasted during braking, especially on the downhill road conditions.Â Keywords: Braking Energy, Regenerative Braking System (RBS), Antilock Braking System (ABS), Modelling ,Simulation.